1999
DOI: 10.1159/000045393
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Induces a Hypertrophic, Senescent Mesothelial Cell Phenotype after Long in vivo Exposure

Abstract: Previous studies, done using our mouse model for population analysis of the mesothelium, showed evidence indicating that in vivo, long-term exposure (up to 30 days) of the peritoneum to high-glucose (4.25% D-glucose) concentration dialysis solutions resulted in a hypertrophic mesothelial phenotype characterized by increased cell surface area, multinucleation, low proliferative capabilities, reduced cell viability, and enhanced enzymatic activity. These elements that define a senescent population of cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…Moreover, our results are in keeping with the observations of Gotloib et al, who detected the appearance of mesothelial cells with the senescent-like phenotype in mice treated chronically with high intraperitoneal load of glucose. 5,27,28 Interestingly, both the in vivo studies and our in vitro experiments showed no significant effect of M, which points to a specific metabolic effect of glucose, unrelated to corresponding hyperosmolality. The peritoneal mesothelium is regarded as a slowly renewing tissue with the basal mitotic activity present in less than 1% cells.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, our results are in keeping with the observations of Gotloib et al, who detected the appearance of mesothelial cells with the senescent-like phenotype in mice treated chronically with high intraperitoneal load of glucose. 5,27,28 Interestingly, both the in vivo studies and our in vitro experiments showed no significant effect of M, which points to a specific metabolic effect of glucose, unrelated to corresponding hyperosmolality. The peritoneal mesothelium is regarded as a slowly renewing tissue with the basal mitotic activity present in less than 1% cells.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, the detrimental impact of high glucose (HG) on mesothelial cells may contribute to the peritoneal membrane dysfunction during dialysis. In a series of experiments, Gotloib et al 4,5 analyzed the imprints of the mesothelium obtained from mice exposed chronically to glucose-containing PDF. They found a significant increase in both the average size of mesothelial cell and the prevalence of very large cells, which together resulted in reduced density of the mesothelial monolayer.…”
mentioning
confidence: 99%
“…Astragalus injection has only been used in peritoneal dialysis therapy [29] . Studies on Astragalus injection were mainly concentrated on its immunomodulating functions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our observations may impact on peritoneal dialysis fluid biocompatibility testing. It has been observed that peritoneal mesothelial cells exposed chronically to dialysis fluids develop a senescence-like phenotype (16). We have previously demonstrated that glucose (a basic component of dialysis solutions) may accelerate the development of senescence features in mesothelial cells, largely by exacerbating oxidative stress (22).…”
Section: Ink4amentioning
confidence: 99%